THE FINANCIAL ORGANIZATION OF INFORMAL WORKERS AT THE POPULAR SHOPPING IN FEIRA DE SANTANA - Nadine de Moura Barbosa, Gesiele (Revista Gênero e Interdisciplinaridade, 2022)
The present work is the preliminary result of an extension experience that sought to understand the economic and financial organization of black women informal workers in the Feirense trade. With that, brief considerations will be made about the observed facts, as well as the theoretical analysis that involves the themes related to the research carried out concurrently with the extension. This expanded summary has a single section in addition to the introduction, methodology, and conclusion. Therefore, its organization prioritizes the presentation of general aspects of informal work and its characteristics in the Brazilian context, then the explanation of the circumstances of the research and of the black women who participated in the project and, finally, the analysis of the financial organization of these women. from what was observed in the extension experience. Thus, the narratives of these women reveal uncertainties, mainly because they constitute a moment of political disputes, adaptation to the new location and new circumstances.